Efficacy of Controlled-Release Urea Fertilizers and Nitrogen Uptake by Rice - Ambra Singh, Kiran Jeet Kaur (2008)
The efficiency of urea fertilizer as Nitrogen (N) source is uncertain as found in many laboratory studies. It is subjected to rapid hydrolysis and NH3-N volatilization. Ideal urea fertilizer should be soluble in soil and continuously regulated in amount that coincides with the rate of plant uptake. Controlled Release Urea (CRU) is a fertilizer that has been amended in such a way that the N is released over a period of time that coincides with plant requirement. This is achieved by coating the urea granule with material such as polymer that regulates the N releases to the soil solution. The CRU releases nutrients during the entire growing-season, reduces N loss and increases yield. Studies of behavior of CRU under tropical condition are limited. With this in view, this study was carried out with the main objective; to identify efficient CRU on selected soils. Laboratory and field studies were undertaken to evaluate the physical and chemical properties of CRU, to quantify the N transformation of CRU on selected Malaysian soils and to detennine yield and N uptake by rice from CRU. Six types of CRU used were CDU Uber-l0, Meister-20, Meister-27, Humate Coated Urea, Duration Type-V, Sulfur Coated Urea (Gold N) and Urea fertilizer as control. Laboratory evaluation was carried out on seven types of soil series; Serdang series (Typic Paleudult), Munchong series (Typic Hapludox), Segamat series (Typic Hapludox), Selangor series (Typic Tropaquept), Rengam series (Typic Kandiudult), Holyrood series (Typic Kandiudult) and Bakau series (Typic Tropaquept). The measurements of thickness of CRU coating and microphotographic observation of the coating were performed using Scanning Electron Microscope. The thickness of fertilizer coatings was in the range from 16.7 um - 73.2 um depending on the coating type. Humate Coated Urea has the highest value (73.2 um) while the lowest value (16.7 f.UD.) was obtained from Gold-N. No coating was found in Urea granule and COU Uber- 10. Experiment results showed, there were significant differences among treatments in percentage of coating. Highest coating percentage was found in Meister-27 (11.23%) followed by Gold-N (11.20010), Meister-20 (10.53%) and Duration Type-V (6.69010). No coating was found in COU Uber-IO and Humate Coated Urea, therefore are categorized as composite fertilizers. Fertilizer N analyses were carried out and compared with the total N content given by the manufacturers. Total N content of all the CRU analyzed were similar to the manufacturer's values.